Promoted Selective Non-Catalytic Reduction: Prospective Technology for Nitrogen Oxide Reduction - Khandoker Abu' Hossain; Mohammad Nazri Mohd-Jaafar; Farid Nasir Ani (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
Promoted selective non-catalytic reduction (SNCR) of nitric oxide (No) has been studied experimentally by injecting aqueous urea solution with and with;ut additive in a pilot-scale diesel-fired tunnel furnace at 3-4 % excess oxygen level and with low ppm of baseline NO, ranging from 65 to 75 ppm within the investigated temperature range. The tests were carried out using commercial grade urea as NO -reducing agent and commercial grade sodium carbonate (NazCO) as additive. The f rnace simulated the small-scale combustion systems where (a) operating temperatures are usually within 973-1,323 K and (b) NO,-emission level remains below 100 ppm. In the SNCR process with 5% urea solution, at normalized stoichiometric ratio (NSR) of 4, as much as 54% reduction was achieved at 1,128 K; while in the promoted SNCR process using NazC03 additive, NO, reduction improved to as much as 69% at 1,093 K In addition, the effective temperature window as well as peak temperature of NO, reduction shifted towards lower temperatures in promoted SNCR These results were significant especially for the investigated level of baseline NO.. The ammonia slip measurements showed that in both cases the slip was below 16 ppm at an NSR of 4 and an optimum temperature of NO, reduction. The investigations demonstrated that urea-based promoted SNCR may be used for small-scale combustion applications and that commercial grade NazC03 is a potential additive.